Analysis of Mathematical Communication Ability based on Students' Self -Esteem in CORE Learning with Positive Feedback. (Universitas Negeri Semarang, 2022)
This study aims to describe mathematical communication skills based on students' self-esteem in the CORE learning model with positive feedback. The research was conducted in class VIII of the Indonesian Institute of Middle School in Semarang with the selection of research subjects based on the results of the questionnaire scores so that high, medium, and low self-esteem groups were obtained. Determination of research subjects using a purposive sampling technique that selects two students in each group. Data analysis of mathematical communication abilities based on student self-esteem in CORE learning with positive feedback using triangulation from questionnaires and written test results with interviews. The results of the study show that CORE learning with positive feedback can improve mathematical communication skills. Mathematical communication skills with high self-esteem fulfill four indicators fulfilled on one subject, and other subjects fulfill three indicators. Students in the moderate self-esteem category can fulfill three indicators on one subject and two indicators on another issue. Students in the low self-esteem category achieve two indicators on one subject and one indicator is performed on another issue. So, the higher the level of self-esteem, the higher the students' mathematical communication skills.